Level of opposition constrains offensive performance in consecutive game situations. An analysis according to game principles. (4th May 2022) - Práxedes, Alba; Pizarro, David; Travassos, Bruno; Domínguez, Miguel; Moreno, Alberto
ABSTRACT: Background: In the last few decades, Nonlinear Pedagogy (NLP) has emerged with the goal to promote a holistic approach through the use of Small-Sided Games (SSG), to optimize specific tactical defensive and offensive behaviours of players. These SSG are designed through the manipulation of relevant task constraints. Specifically, the balance on the number of outfield players is a constraint that has been recently studied because it can change players' behaviour. However, most of the studies in this domain have only analysed the acute effects of the manipulation of different SSG without any idea about the implications for learning or to improve the transfer between practice tasks to the context of performance. Purpose: The main purpose of this study was to understand the effect of the use of a task of numerical superiority in attack (5 vs 4; NS) before a task of equal number of player in comparison with the use of only two numerical equality (5 vs 5; NE) tasks. A second objective was to examine this effect according to the game principles: keep the ball possession and progress to the goal. Method: Twenty footballers (U14 yrs), grouped in teams of five players, participated in this study. Each team performed two different sequences of SSG (NS + NE and NE + NE) and in two different conditions regarding the game principle. 2176 actions were analysed. Decision-making was measured through the GPET instrument. Also, it was assessed the duration of ball possession and the number of ball touches through a hand notation analysis system. Results: Results show a tendency to decrease the offensive performance in the sequence (NS + NE). However, if we compare both initial situations, significant higher values were observed in the situation with NS. In addition, regarding the two final situations, there are hardly any differences between them. Conclusion: This study highlighted some key pedagogical principles of the constraints-led approach for designing training environment in team games. Coaches in formative stages should promote unequal game situations with superiority number of players in attack, to facilitate the decision-making and develop the technical skills thanks to a greater participation and a greater duration of ball possession. As learning progresses, coaches should design equal situations to facilitate an adaptation to the real game and promote long-term adaptations on players' performance. Finally, the game principle is another constraint to take into account since it promotes variability and boosts the discovery and exploration of players' movement solutions.